The Development of Assessment Instrument to Assess Implementation of Work-Based Learning, and Learning Innovation Skills - Irma Manda Negara; Nurul Hidayati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This article aims to develop an instrument to assess the implementation of a Work-Based Learning internship approach, and learning innovation skills by referring to the Framework of Partnership 21 Century Skills. This research was a Research and Development (R&D). The development was carried out through four phases; Preliminary Investigation, Design, Realization, and Development. The instruments developed were tried out to students who had already carried out an internship. This study conducted 3 tests of validity, namely expert validity, content validity, and criterion validity. Then, reliability testing uses Cronbach's Alpha. The WBL variable had a reliability of 0.942 and a LIS variable of 1,000, Hence, it can be concluded that the instrument developed was declared valid and reliable to assess students' WBL and LIS activities. Keywords: Work Based Learning, Innovation Skills of Students, Development Assessment Instrument